Kajian Lingkungan Pengendapan Berdasarkan Karakteristik Batubara Formasi Pulau Balang - Fungky Suhayadi; Sriyanti (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Coal has certain physical and chemical properties, from these properties coal can be used as a parameter to determine coal classification based on rank. Balang Island is a coal-bearing formation in the Kutai Basin. To determine the depositional environment, coal samples were taken. From the sample, coal characteristics such as water content, volatile matter, calorific value, maceral and mineral composition were produced. From these characteristics, coal rank can be determined. Determination of the depositional environment based on the 1986 Diesel diagram (in Lamberson, 1991) and based on the 1978 Horne Classification. Coal based on the reflectance value of vitrinite includes the rank of Sub-bituminous C and Lignite A, with an average value of 0.372%, based on the calorific value included in the Bituminous High Volatile C. with an average value of 11,902 Btu/lb – 12,447 Btu/lb on a daf basis. The fuel ratio with a value of 0.90 – 0.98 is included in the Bituminous coal rank. The location of coal deposition is dominated by shrubs 48.8% and woody plants 26.32%, so that the deposition location is likely to be deposited in the fen location which is a swamp location dominated by shrubs and few trees. From the Tissue Preservation Index values of 0.424 – 1.074 and Gelification Index 3.481 – 14,815, the coal was deposited in the lower and upper delta plain depositional environments. Abstrak. Batubara memiliki sifat fisik dan kimia tertentu, dari sifat tersebut batubara dapat dijadikan parameter untuk menentukan klasifikasi batubara berdasarkan peringkat. Pulau balang merupakan formasi pembawa batubara yang berada pada cekungan kutai. Untuk menentukan lingkungan pengendapannya, dilakukan pengambilan sampel pada batubara. Dari sampel tersebut dihasilkan karakteristik batubara seperti kadar air, volatile matter, nilai kalor, komposisi maseral dan mineral. Dari karakteristik tersebut dapat ditentukannya peringkat batubara. Penentuan lingkungan pengendapan berdasarkan diagram Diessel 1986 (dalam Lamberson, 1991) dan berdasarkan Klasifikasi Horne 1978. Batubara berdasarkan nilai reflektansi vitrinit termasuk peringkat Sub-bituminous C dan Lignite A, dengan rata–rata nilai 0,372%, berdasarkan nilai kalor termasuk kedalam Bituminous High Volatile C. dengan nilai rata – rata sebesar 11.902 Btu/lb – 12.447 Btu/lb dalam basis daf. Fuel ratio dengan nilai 0,90 – 0,98 termasuk kedalam peringkat batubara Bituminous. Lokasi pengendapan batubara didominasi oleh tumbuhan perdu 48,8% dan tumbuhan kayu 26,32%, Sehingga lokasi pengendapan kemungkinan terendapkan lokasi fen yang merupakan lokasi rawa didominasi oleh tanaman perdu dan sedikit pohon. Dari nilai Tissue Preservation Index 0,424 – 1,074 dan Gelification Index 3,481 – 14,815, batubara terendapkan pada lingkungan pengendapan lower dan upper delta plain.